2021
DOI: 10.48550/arxiv.2107.02775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Countering Misinformation on Social Media Through Educational Interventions: Evidence from a Randomized Experiment in Pakistan

Abstract: Fake news is a growing problem in developing countries with potentially far-reaching consequences. We conduct a randomized experiment in urban Pakistan to evaluate the effectiveness of two educational interventions to counter misinformation among low-digital literacy populations. We do not find a significant effect of video-based general educational messages about misinformation. However, when such messages are augmented with personalized feedback based on individuals' past engagement with fake news, we find a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…We find that less digitally literate users are more likely to express non-neutral emotional reactions to news. This is consistent with a digital media literacy intervention, which reduced non-neutral emotional reactions to news headlines in a randomized experiment in Pakistan (Ali and Qazi, 2021). However, we did not find a statistically significant association between digital literacy and confirmation bias, that is, whether people consider a headline to be true or false due to its alignment with their prior beliefs.…”
Section: Jqd: Dm 2(2022)supporting
confidence: 85%
See 2 more Smart Citations
“…We find that less digitally literate users are more likely to express non-neutral emotional reactions to news. This is consistent with a digital media literacy intervention, which reduced non-neutral emotional reactions to news headlines in a randomized experiment in Pakistan (Ali and Qazi, 2021). However, we did not find a statistically significant association between digital literacy and confirmation bias, that is, whether people consider a headline to be true or false due to its alignment with their prior beliefs.…”
Section: Jqd: Dm 2(2022)supporting
confidence: 85%
“…Badrinathan (2021) found no effect of an in-person media literacy training on truth discernment in a low digital literacy sample in India. Ali and Qazi (2021) found that video-based messages aimed at teaching people how to spot fake news augmented with personalized feedback improved accuracy of beliefs about fake news among low digital literacy users in Pakistan.…”
Section: Jqd: Dm 2(2022)mentioning
confidence: 97%
See 1 more Smart Citation
“…Alternative data collection methods such as phone surveys are much more difficult to conduct, and can be expensive. Importantly, what works in the West may not work elsewhere: interventions that were shown to be effective in Western countries did not yield the same results in countries such as India (Badrinathan, 2021;Guess et al, 2020) and Pakistan (Ali & Qazi, 2021). As Ali and Qazi (2021) note: the effectiveness of interventions "critically depends on how well their features and delivery are customised for the population of interest".…”
Section: Recommendations For Policymakers and Tech Companiesmentioning
confidence: 99%
“…Importantly, what works in the West may not work elsewhere: interventions that were shown to be effective in Western countries did not yield the same results in countries such as India (Badrinathan, 2021;Guess et al, 2020) and Pakistan (Ali & Qazi, 2021). As Ali and Qazi (2021) note: the effectiveness of interventions "critically depends on how well their features and delivery are customised for the population of interest". Similarly, automated solutions may work well in English, but are typically not highly advanced in other languages.…”
Section: Recommendations For Policymakers and Tech Companiesmentioning
confidence: 99%